First report of jackfruit decline caused by Phytophthora spp. in Bangladesh - Jenny, Farhana; Kader, Md Abdul; Bhuiyan, Md Abdullahil Baki (Fundamental and Applied Agriculture, 2020)
A survey was conducted at Gazipur, one of the major jackfruit producing districts in Bangladesh where decline symptomps of jackfruit trees were observed. The characteristic symptoms of jackfruit decline included trunk canker, wilting, dieback of the canopy and in some cases complete death. The disease incidence was increased with the increase of plants age. Among the isolated fungi from the study area, only Phytophthora spp. were found to be pathogenic and caused decline symptoms in artificially inoculated jackfruit seedlings. Based on the morphological data, the isolates were confirmed as Phytophthora spp. To the best of our knowledge this is the first report of Phytophthora spp. causing the decline of jackfruit trees in Bangladesh.